PENGESAHAN ANAK ZINA MENURUT PUTUSAN MAHKAMAH KONSTITUSI DALAM PERSPEKTIF MAQASHID SYARIAH - Hamdah Faridah; Muhamad Mustahal; Fathudin (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Constitutional Court Decision Number 46/PUU-VIII/2010 is the state's legal response to the need for legal protection for children born out of wedlock. This decision expands the civil relationship between illegitimate children and their biological fathers based on scientific evidence, without being intended as a validation of Islamic lineage. This study aims to analyze the legal implications of this decision in the national legal system and examine it through the perspective of Maqashid Syariah, specifically the balance between the protection of the child's life and rights (hifz al-nafs) and the protection of descendants (hifz al-nasl). The method used is normative legal research with a statutory and conceptual approach, accompanied by an analysis of the ratio decidendi of the Constitutional Court decision. The results of the study indicate that the expansion of civil relationships is a form of legal responsibility of biological fathers and is not identical to the determination of lineage in Islamic law. Through the Maqashid Syariah approach, this decision can be understood as a state legal ijtihad to protect children's rights without violating the basic principles of Islamic lineage..